Manufacture of Fiber Ropes Made from The Inner Bark of Melinjo Stem (Gnetum gnemon) - Bela Velila Viska Yunita; Saipul Bahri Daulay; Ainun Rohanah (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Melinjo plant has a very high quality of fiber that found in the inner bark of  the stem that can be made as a rope as a substitute to synthetic ropes that can decrease environmental pollution. The research was aimed to make a fiber rope from the inner  bark of melinjo  stem and to test the endurance of the rope toward a tensile test. The research had been conducted at Agriculture Engineering Laboratory, College of Agriculture, USU and tensile test was conducted at Research Laboratory, College of Engineering, USU in March-July 2015 using spinners simple tool in making the rope and tensile test to determine the strength of the rope toward burden. Parameter  measured were tensile stress, strain, elasticity, ropes deformation, and malleability. The results showed that heterogeneous fiber caused different rope diameter and affect the value of parameters measured. From the ropes test it was found that  average tensile stress was 42.38 N/mm2, strain was 0.3742, ropes deformation was 35.17867 mm, elasticity was 114.1673 N/mm2 and malleability was 37.42 %. Key Words : Natural fiber, rope, inner bark of melinjo stem, spinning, tensile test.